Temporal assessment of fish distribution and abundance in a hypersaline embayment, Hamelin Pool, Shark Bay, Western Australia - Richards, K.E.; Campbell, K.L.; Saunders, Ben; Suosaari, E.P.; Wilson, S.K.; Harvey, Euan (2025)
Hamelin Pool Marine Nature Reserve is a hypersaline environment within Shark Bay UNESCO World Heritage Area, on the remote west coast of Australia. This unique embayment is home to the world's largest population of stromatolites, globally significant seagrass beds, and is protected from fishing, yet little is known of its fish assemblages. Baited remote underwater stereo-video systems (stereo-BRUVs) were deployed within Hamelin Pool four times over six years (2016, 2018, 2020 and 2022) and across four habitat types (low relief stromatolites (LRS), high relief stromatolites (HRS), sand and seagrass). We aimed to assess the fish assemblages and examine temporal differences in the structure and size classes in relation to changing habitats. A total of 44,649 fish from 79 species (46 Families) were recorded from 624 stereo-BRUVs deployments. Three species dominated the fish assemblage accounting for 60 % of all fish recorded (Atherinidae spp 21 %, Helotes octolineatus 20 %, Pentapodus vitta 18 %). The majority of fishes were either generalist invertebrate feeders (40 %) or generalist carnivores (29 %). Fish assemblage structure differed among years, habitats and site, although ‘year’ had minimal influence on the assemblage variation (2 %) compared to ‘habitat’ (14 %) and ‘site’ (26 %). Across all four sampling years, the abundance and number of species of fish was consistently greatest within seagrass habitats, with the composition of these assemblages accounting for 65 % of the variation between habitats. The commercially valuable Chrysophrys auratus showed evidence of growth to reproductive size and therefore may act as a potential source of larvae. Despite being a habitat suboptimal for many species, Hamelin Pool's fish assemblages are stable in terms of their abundance and diversity. However, there are significant differences in the composition of assemblages between habitats, as well as variations in size distributions, suggesting this hypersaline environment supports fish growth and may facilitate replenishment of species fished in the wider Shark Bay area.